Effect of acid hydrolysis on the tableting properties of chitin obtained from shrimp heads (2015)
ABSTRACT: To assess the effect of acid hydrolysis on the degree of acetylation, crystallinity, and molecular weight of chitin obtained from shrimp heads as well as to evaluate their tableting properties. Methods: The effect of acid hydrolysis conditions such as reaction temperature (46, 60, 80, 100, 114°C), hydrochloric acid concentration (4.6, 6, 8, 10 and 11.4 M) and reaction time (0.6, 2, 4, 6 and 7.4h) were examined. The degree of acetylation and molecular weight were found by Fourier transform spectroscopy (FT-IR) and viscometry methods, respectively. The degree of crystallinity degree and its compact tensile strength were determined by x-ray and Fell & Newton methods, respectively. Results: The combined effect of high temperature (> 80 oC), HCl concentration (> 2 M) and reaction time (> 4 h) led to high depolymerization, reduction in degree of acetylation, crystallinity, chitin yield and thus, decreased tensile strength and accelerated compact disintegration time. Optimal reaction conditions were achieved at an acid concentration of 2.2 M, temperature of 60 oC and reaction time of 4 h. These conditions rendered compacts with tensile strength of 25.7 MPa and disintegration time of 25.3 min. Conclusion: The optimal HCl hydrolysis conditions for shrimp heads rendered chitin suitable for the preparation of compacts with good tensile strength and moderate disintegration time.